Revision of the subgenus Cosmiomorpha (Cosmiomorpha)(Coleoptera: Scarabaeidae: Cetoniinae) - Qiu, Jian-Yue; Xu, Hao; Hu, Chun-Lin (Zootaxa, 2013)
A taxonomic revision of the subgenus Cosmiomorpha (Cosmiomorpha) Saunders is presented. Seven species are recognized, including four described herein, C. fortis new species, C. nigripedis new species, C. maolanensis new species, and C. cheni new species all from China. Cosmiomorpha baryi Bourgoin and C. squamulosa Schürhoff are placed as junior synonyms of C. decliva Janson, and C. angulosa Fairmaire as a synonym of C. decliva is also confirmed. Lectotypes are designated for C. decliva Janson, C. angulosa Fairmaire, and C. squamulosa Schürhoff. Color photographs and diagnoses of all species are provided, with comments on intraspecific variations. A key to males is also presented. Localities of “Siào-Lòu” and “Se Pin-Lou Chan” are discussed with a map.